ANALISIS PENGARUH STRES KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. INDOPELITA AIRCRAFT SERVICES - Ali Zaenal Abidin; Sarwani .; Umi Rusilowati (Inovasi, 2015)
ANALYSIS OF EFFECT OF WORK STRESS AND WORK ON THE PERFORMANCE OF EMPLOYEES MOTIVATION (CASE STUDY IN. INDOPELITA AIRCRAFT SERVICES). The purpose of this study is to investigate the phenomenon and to obtain empirical evidence, and conclusions about the effects of two independent variables mentioned above, the performance of employees. This research uses descriptive quantitative method. The type of data used are primary data. The sample used by 95 respondents. Methods of collecting data is done through the distribution of questionnaires to scale linkert. The results showed that (1) the stress of work a significant negative effect on the performance of employees. Contributions effect of work stress on employee performance for 0063. This means that variations in the performance of employees affected by changes in work stress by 6.3%, (2) work motivation positive and significant effect on employee performance. Contributions influence work motivation on employee performance at 0:07. This means that variations in the performance of employees affected by changes in motivation to work by 7%, (3) Work stress and work motivation simultaneously and significant influence on employee performance. Contributions effects of job stress and work motivation simultaneously by 0115. This means that the variation changes the employee's performance is affected by the stress of work and work motivation by 11.5% while the remaining 88.5% is influenced by other factors not included in the scope of this study. From the data analysis it can be concluded that the stress of work and work motivation parsiel or simultaneously significant effect on performance. From the results of the descriptive analysis, it is suggested that in order to reduce employee stress, the work time should receive special attention. Keywords: job stress, motivation and performance of employees